Current Progress in Developing Plant Extract-Based Hepatoprotective Drugs to Prevent Drug-Induced Liver Injury During Tuberculosis Treatment: A Literature Review - Fenny, Fenny; Joan, Joan; Sanjaya, Ardo; Gunadi, Julia Windi (Faculty of Medicine Universitas Sebelas Maret, 2025)
Introduction: Anti-tuberculosis treatment (ATT) can cause drug-induced liver injury. This complication leads to disruption of tuberculosis treatment. Therefore, plant extract-based is useful in a way to prevent drug-induced liver injury due to ATT. Methods: This review source came from PubMed and Google Scholar. We found 59 articles with the keywords “drug-induced liver injury” AND “hepatotoxicity” in the range 2014-2024. We selected 12 articles to be reviewed in this article. Result: Plant extract-based in this article has several mechanisms to prevent drug-induced liver injury due to ATT. All of them contain high antioxidants. Silymarin works by blocking the effects of the enzymes catalase and glutathione peroxidase, as well as suppressing the action of lipid peroxidase which causes liver damage. Jujube, Lasianthera africana, and Telfairia occidentalis can neutralize free radicals. Trapa natans and Bacopa monnieri work from the glutathione (GSH) pathway. Bacoside and Tamarix gallica mechanisms to prevent liver injury are still unknown. Most of the herbs can decrease levels of AST, ALT, and ALP as biomarkers of liver injury significantly. Conclusion: Many plant extracts have the potential to prevent the incidence of drug-induced liver injury caused by ATT both in animal models and clinical trials. However, adequate dosing and sample size are required to make sure that the effects are significant.